2012
DOI: 10.5045/kjh.2012.47.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Castleman disease

Abstract: Castleman and Towne described a disease presenting as a mediastinal mass resembling thymoma. It is also known as "giant lymph node hyperplasia", "lymph node hamartoma", "angiofollicular mediastinal lymph node hyperplasia", and "angiomatous lymphoid hyperplasia". The pathogenesis is unknown, but the bulk of evidence points toward faulty immune regulation, resulting in excessive B-lymphocyte and plasma-cell proliferation in lymphatic tissue. In addition to the mediastinal presentation, extrathoracic involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 121 publications
0
77
0
7
Order By: Relevance
“…Данный вирус чаще выявляется у больных БК, серопозитивных по ВИЧ (по данным Н. El-Osta и соавт. [14], в 100% случаев), одна-ко описаны случаи инфицированности HHV-8 и у сероне-гативных по ВИЧ пациентов [15][16][17][18][19][20][21].…”
Section: контактная информацияunclassified
See 1 more Smart Citation
“…Данный вирус чаще выявляется у больных БК, серопозитивных по ВИЧ (по данным Н. El-Osta и соавт. [14], в 100% случаев), одна-ко описаны случаи инфицированности HHV-8 и у сероне-гативных по ВИЧ пациентов [15][16][17][18][19][20][21].…”
Section: контактная информацияunclassified
“…Морфологическая картина в ЛУ напоминала тако-вую при ПКВ, но имела отличие: в мантийной зоне содер-жатся крупные плазматические клетки -плазмобласты с обильной цитоплазмой и заметными одним или несколь-кими ядрышками [22][23][24]. Поэтому в настоящее время авторы предпочитают классифицировать БК в соответ-ствии с гистопатогенным типом на ГВВ, ПКВ, МБК и ас-социированный с HHV-8 (плазмобластный) варианты (в противоположность традиционной уницентрической/ мультицентрической модели) [15][16][17][18][19][20][21].…”
Section: контактная информацияunclassified
“…It was reported that calcification might be observed in 5%-10% of patients. On the other hand, multicentric lesions can typically be observed in the form of bilateral hilar and mediastinal lymphadenopathy, centrilobular nodular opacity, and rarely ground glass, consolidation, and bronchiectasis (10,12). The value of PET in diagnosis is disputed, as it is not able to distinguish between malignant disease and CD.…”
Section: Discussionmentioning
confidence: 99%
“…Hilar CD can be confused with lung cancer. It is rarely located in pleural, pericardial, intercostal, and intrapulmonary areas (5,10,11). Thorax CT scans identified 3 presentations for the localized form of the disease: solitary noninvasive masses were most prevalent (50%), followed by infiltrative masses accompanied by lymphadenopathy (40%) and lymphadenopathy with no masses (10%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation